Crossing the threshold of general public relations practices: assessing Malaysia's experience in the first quarter of the millennium - Abdul Rahman, Saiful Nujaimi; Hashim, Norliana (Human Resource Management Academic Research Society, 2022)
Public Relations (PR) is nothing new to the present day global community. In fact, mankind had exercised PR since the day they first decided to live together. Since then, an essential beacon of wisdom in the history of mankind was planted. The birth of the modern PR began in 1948 when the Public Relations Society of America and the Institute of Public Relations in Britain were founded. Today, the influence of this communication field has engulfed almost all professions of global organizations. Majority of these organizations apply the PR principles and practices into their organizational structures. This paper begins with the historical backgrounds of the international PR culture, studies, and definitions. From there, the discussion penetrates deeper into the realm of the Malaysian PR culture. This analysis deals with many aspects of the PR, i.e. professional ethics, social and legal contracts, aimed at giving a considerably critical understanding of the Malaysian PR culture, which differs in definitions and practices. At the end of this paper, readers are presented with an overview of contemporary threats and challenges facing the field. This concept paper deals with the past, the present, and the future uncertainties of the PR field. Whether we are aware or not, PR today has been tremendously used for managing social stress in view of globalization. Yet, the forces of tolerance and brotherhood grant the country confidence in facing future challenges and threats. Indeed, the world of global PR is changing inconsiderately. Come what may, Malaysian has chosen to toughen up for a journey of her own in the wake of PR uncertainties.